Influence of warm-up duration on perceived exertion and subsequent physical performance of soccer players - Yanci, J.; Iturri, J.; Castillo, D.; Pardeiro, M.; Nakamura, F. Y. (Biology of Sport, 2019)
The aim of this study was to analyse the effects of three warm-up protocols with different durations in semi-professional soccer players. Fifteen semi-professional soccer players performed three warmup protocols (Wup25min: 25 min, Wup15min: 15 min and Wup8min: 8 min duration) on three different days. Before (pre-test) and after (post-test) each warm-up protocol, the players` physical performance (sprint, vertical jump and change of direction) was evaluated and all the players were asked to respond to the subjective scale of readiness to play a match. Also, after completing each warm-up protocol, all players responded to the rating of perceived exertion (RPE) scale. Although all protocols significantly improved the feeling of players being prepared to play the game (p< 0.05) than in the Wup15min and Wup8min protocols. The Wup8min protocol was the only one that improved the acceleration ability of the soccer players in this study.